Design and Implementation of Aquascaping Automation System Using Arduino Uno R3 - Musa, Wahab; Abdussamad, Syahrir; Dako, Amirudin Yunus; Nasibu, Iskandar Zulkarnain; Tansa, Salmawaty; Ingopo, Renaldi Anwar (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
One of the arts in creating a beautiful natural environment in an aquarium is aquascaping. It requires good planning in the placement of water, rocks, plants and animals in the aquarium. In addition, it is necessary to control the acidity level (pH) of the water so that it is in a stable condition needed by the flora and fauna in the aquarium. In this research, automatic control is implemented using an Arduino Uno R3 for the pH sensor. This Arduino Uno R3 is used to control pH, temperature, and lighting. The ideal temperature in aquascaping is kept at 220C - 250 C by controlling it through a DC fan, and the pH of the water is controlled through a water pump. With this automatic control, aquarium owners can save on monitoring costs and time compared to manual methods.Salah satu seni dalam menciptakan lingkungan alam yang indah di dalam akuarium adalah aquascaping. Diperlukan perencanaan yang baik dalam penempatan air, bebatuan, tanaman dan hewan di dalam akuarium. Selain itu, perlu adanya pengontrolan tingkat keasaman (pH) air agar berada dalam kondisi stabil yang dibutuhkan oleh flora dan fauna di dalam akuarium. Pada penelitian ini, kontrol otomatis diimplementasikan dengan menggunakan Arduino Uno R3 untuk sensor pH. Arduino Uno R3 ini digunakan untuk mengontrol pH, suhu, dan pencahayaan. Suhu ideal pada aquascaping dijaga pada suhu 220C - 250 C dengan mengontrolnya melalui kipas DC, dan pH air dikontrol melalui pompa air. Dengan kontrol otomatis ini, pemilik akuarium dapat menghemat biaya dan waktu pemantauan dibandingkan dengan metode manual.